Tuning flux: autophagy as a target of heart disease therapy - Xie, Min (2011)
PURPOSE OF REVIEW: Despite maximum medical and mechanical support therapy, heart failure remains a relentlessly progressive disorder with substantial morbidity and mortality. Autophagy, an evolutionarily conserved process of cellular cannibalization, has been implicated in virtually all forms of cardiovascular disease. Indeed, its role is context dependent, antagonizing or promoting disease depending on the circumstance. Here, we review current understanding of the role of autophagy in the pathogenesis of heart failure and explore this pathway as a target of therapeutic intervention. RECENT FINDINGS: In preclinical models of heart disease, cardiomyocyte autophagic flux is activated; indeed, its role in disease pathogenesis is the subject of intense investigation to define mechanism. Similarly, in failing human heart of a variety of etiologies, cardiomyocyte autophagic activity is upregulated, and therapy, such as with mechanical support systems, elicits declines in autophagy activity. However, when suppression of autophagy is complete, rapid and catastrophic cell death occurs, consistent with a model in which basal autophagic flux is required for proteostasis. Thus, a narrow zone of ‘optimal’ autophagy seems to exist. The challenge moving forward is to tune the stress-triggered autophagic response within that ‘sweet spot’ range for therapeutic benefit. SUMMARY: Whereas we have known for some years of the participation of lysosomal mechanisms in heart disease, it is only recently that upstream mechanisms (autophagy) are being explored. The challenge for the future is to dissect the underlying circuitry and titrate the response into an optimal, proteostasis-promoting range in hopes of mitigating the ever-expanding epidemic of heart failure.